2019
DOI: 10.1177/0886260519865960
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors Among Palestinian Women Living in a Context of Prolonged Armed Conflict and Political Oppression

Abstract: Research has widely documented the effects of war and political violence on the functioning and well-being of adults and children. Yet, within this literature, women’s agency in the face of war-related adversity and political violence remains underexplored. The present study was conducted in the Gaza Strip in the aftermath of the most recent war on Gaza in 2014, with the aim of investigating the consequences of war and political violence for women’s mental health and psychological functioning. Based on intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 120 publications
(130 reference statements)
0
34
0
Order By: Relevance
“…This kind of violence against women is forbidden under international humanitarian law [ 36 ]: Rule 93 of this document states that rape and other forms of sexual violence are prohibited [ 78 ]. In addition to that, studies of environments of armed conflict also indicates that women are more predisposed than men to feel distress and develop mental illness in such situations, including post-traumatic stress disorder (PTSD) [ 79 , 80 , 81 , 82 , 83 ].…”
Section: Science Mapping Of Human Rightsmentioning
confidence: 99%
“…This kind of violence against women is forbidden under international humanitarian law [ 36 ]: Rule 93 of this document states that rape and other forms of sexual violence are prohibited [ 78 ]. In addition to that, studies of environments of armed conflict also indicates that women are more predisposed than men to feel distress and develop mental illness in such situations, including post-traumatic stress disorder (PTSD) [ 79 , 80 , 81 , 82 , 83 ].…”
Section: Science Mapping Of Human Rightsmentioning
confidence: 99%
“…Research on women's psychological experience in Palestine suggests that for women in this context, motherhood appears to be central to (though certainly not the only factor within) relationships among political violence, trauma, and resilience (Giacaman & Johnson, 2013;Peteet, 1997;Shalhoub-Kevorkian, 2006;Veronese, Cavazzoni, Russo, & Sousa, 2019). Qualitative studies have found that mothering in Palestine generates ongoing guilt, fear, and hopelessness due to the impossibility of protecting children from the trauma and humiliation of political violence-while also providing an amplified sense of purpose and meaning for women (Akesson, 2015;Punamäki, 1987;Roth, 2015;Shalhoub-Kevorkian, 2003).…”
Section: Geo-political Context Of Mothering In Palestinementioning
confidence: 99%
“…From Albert Bandura's (1989Bandura's ( , 1999 early studies in the field of social-cognitive psychology to more recent contributions amongst psychology, sociology, and social geography (Abebe, 2019;Cavazzoni et al, 2021;Steckermeier, 2019;Veronese et al, 2018), the concept of agency defined as 'people's ability to exert control over one's life and pursue goals' has been explored and investigated within different contexts, countries, and populations. So far, several contributions have documented agency in people living in areas of conflict, poverty or marginalization (Gigengack, 2014;Klocker, 2007;Veronese et al, 2019aVeronese et al, , 2019b or among women across the globe (James-Hawkins et al, 2018;Kabeer, 1999;Martin & Phillips, 2017;Veronese et al, 2019a), highlighting participants' actions and reactions concerning situations of oppression or structural violations experienced in everyday life. Moreover, most recently, a major focus of agency also occurs within New Studies on Childhood (Prout & James, 1997), which have come to highlight children's abilities to give meaning to their life contexts and mobilize resources and survival skills to protect their well-being (Abebe, 2019;Cavazzoni et al, 2020;Edmonds, 2019;Tisdall & Punch, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, for those who approach agency as a construct in its own right, the presence of different definitions in the literature is a source of confusion. At times it is defined in a general and inclusive way as 'the socio-culturally mediated capacity to act' (Ahearn, 2001, p.122) or as 'the ability to define one's goals and act upon them' (Kabeer, 1999, p.438), while others emphasize its strong interconnections with contextual, temporal, and structural aspects (Abebe, 2019;Hitlin & Elder, 2006;Veronese et al, 2019a). This lack of a clear and shared definition is also reflected in the paucity and diversity of attempts at its assessment and by the correspondingly poor development of psychometric measures to do so (Hitlin & Elder, 2006;Kristiansen, 2014;Settersen & Gannon, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation